PERCEPTIONS OF TRADITIONAL MEDICINES FOR SELF-MEDICATION AMONG PEOPLE IN DIENG PLATEAU CENTRAL JAVA PROVINCE, INDONESIA - Aris Widayati; Damiana Sapta Candrasari; Lusia Jois Mariana; Veronica Veronica (Poltekkes Kemenkes Semarang, 2021)
Traditional medicines are commonly used in the community. One type of traditional medicines that is popular among people is